2022
DOI: 10.1002/adfm.202111373
|View full text |Cite
|
Sign up to set email alerts
|

Realizing High‐Performance BiSbTe Magnetic Flexible Films via Acceleration Movement and Hopping Migration of Carriers

Abstract: Improving the thermoelectric (TE) performance of Bi 2 Te 3 -based flexible films remains a huge challenge. Herein, high-performance Ni/epoxy/Bi 0.5 Sb 1.5 Te 3 magnetic flexible TE films are prepared by incorporating Ni nanoparticles (Ni-NPs). Atomic-resolution STEM investigation demonstrates that Te vacancies induced by the orientation reaction between Ni-NPs and Te from Bi 0.5 Sb 1.5 Te 3 trigger the presence of negatively charged ( ) ′′′ ′′′ V V V V B Bi i S Sb b and ( ( ) ) ′ ′ B Bi i S Sb b T Te e T Te e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…[25] The reaction equations are as follows: ′ ′ established atomic-scale micro-electric fields in the carrier transport channel, which can accelerate the carrier movement and cause carrier hopping migration, promoting the increase of carrier mobility. [24] On the other hand, the BST/CoTe 2 /Co heterointerface also produces carrier energy filtering effect, which can effectively scatter low-energy carriers without affecting the high-energy carrier transport. [31][32][33] The M-H curves of Co/BST/PVDF films are shown in Figure 6b-d.…”
Section: Mechanism Of Enhanced Electricalmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] The reaction equations are as follows: ′ ′ established atomic-scale micro-electric fields in the carrier transport channel, which can accelerate the carrier movement and cause carrier hopping migration, promoting the increase of carrier mobility. [24] On the other hand, the BST/CoTe 2 /Co heterointerface also produces carrier energy filtering effect, which can effectively scatter low-energy carriers without affecting the high-energy carrier transport. [31][32][33] The M-H curves of Co/BST/PVDF films are shown in Figure 6b-d.…”
Section: Mechanism Of Enhanced Electricalmentioning
confidence: 99%
“…[19][20][21][22][23] Recently, our group found that magnetic metal nanoparticles Co and Ni can undergo in situ reaction and orientation reaction with Bi 0.5 Sb 1.5 Te 3 (BST), resulting in accelerated carrier movement and hopping migration, and successfully prepared Bi 2 Te 3 -based flexible magnetic TE films with high electrical transport properties. [24,25] Thus, more and more researches have proved that magnetic recombination is an effective means to improve the electrothermal conversion performance of TE materials. However, how to control the direction of the built-in micro-magnetic field in TEM composites has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…13,27,28 Lately, high-performance thermoelectromagnetic (TEM) lms, developed based on the magnetically enhanced TE effect, [29][30][31] are also proposed as an effective strategy of optimizing the electrical transport properties. 32,33 For example, magnetic metal nanoparticles (NPs) were introduced into Bi 2 Te 3 -based lms, which led to a signicant enhancement in the electrical transport and cooling properties of the prepared TE lms via the thermo-electro-magnetic coupling effect. [33][34][35] These results demonstrate that the presence of certain magnetic properties and conductive channels can signicantly increase the electro-thermal conversion performance, and then a high-performance TEM lm can be created by combining the relevant magnetic properties and conductive channels.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 For example, magnetic metal nanoparticles (NPs) were introduced into Bi 2 Te 3 -based lms, which led to a signicant enhancement in the electrical transport and cooling properties of the prepared TE lms via the thermo-electro-magnetic coupling effect. [33][34][35] These results demonstrate that the presence of certain magnetic properties and conductive channels can signicantly increase the electro-thermal conversion performance, and then a high-performance TEM lm can be created by combining the relevant magnetic properties and conductive channels. However, the impact of structural relationships on the TE properties of multilayer TE lms, which feature a combination of correlated magnetic properties and conductive channels, has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…As both the practical need and the worldwide market for wearable and implantable electronics are increasing rapidly [ 1 , 2 ], flexible thermoelectric (FTE) materials, which are fundamental in the manufacturing of such devices, have been receiving particular attention in recent years. To maximize the electro-thermal conversion efficiency and reachability [ 3 ], the FTE materials should exhibit satisfactory thermoelectric properties at a relatively low temperature range [ 4 , 5 ]. Among all kinds of TE materials, bismuth telluride-based materials are considered some the most attractive and promising FTE materials for both p-type and n-type TE applications to date [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%